O trabalho docente na rede municipal de educação de Goiânia - Morais, Raquel Salomão (2016)
This study is part of the line of research on Labor, Education and Social Movements and aims to understand how teachers perform individualized care, the Municipal Network Goiânia through a case study in a school in the first cycle. The service is offered in order to be a time for students with learning disabilities so that they may have a space to remedy their difficulties. The service is offered for students with learning disabilities so that they may have time and space to remedy their difficulties. The service takes place twice a week for a total of two hours per week. The relationship between what is prescribed for the purposes of answering the teacher's task and what actually happens in reality during its execution, observing what the teacher puts in motion for its realization will be observed, which often extrapolates what is prescribed and many see no setting actions that are invisible in everyday school life. Documents that say something about the service will be analyzed (RME). School history as a formal institution and the teacher's role in dealing with knowledge will also be analyzed. Methodologically held -If observations of care, interviews and instruction to double. The theoretical framework lies in the field of French-based ergonomics and seeks to recognize and locate in this field of study the distance between prescribed work and real work and how this distance is managed by the worker in his work activity.